Report on practice in industry training in fish processing technology - De Guzman, Dulcisima G. (College of Fisheries, University of the Philippines in the Visayas, 1978)
Students of fish processing technology are given the opportunity to acquire more practical insights into the fish processing industry through actual training in different establishments engaged in the same. This valuable exposure is not usually obtained inside the classroom. It helps students obtain practical knowledge about the theories they have learned, and evaluate problems encountered in relation to fish utilization as an industry. This report was made in such a way that all data and observations made by the author are purely for academic purposes. The training was carried out in five different processing plants on freezing, smoking, and fermentation and canning.